A Brief History of Disaster Response and Recovery Efforts at the Newfoundland/Gander International Airport 1941-1985 - Mullaly-Moulton, Betty; Doyle, Emily M. (Newfoundland and Labrador Studies)

(untitled) (Faculty of Arts, Memorial University, 2023)
The Newfoundland Airport, later renamed the Gander International Airport, was built in 1938–39 to deliver regular flight services that supported aircraft refueling stopovers for flights travelling from New York, United States to London, United Kingdom. It is also the site of significant aviation disaster and large-scale emergency events thathave brought the world to Gander (and Gander to the world), including the Arrow Air Flight 1285 crash in 1985 and the accommodation of diverted aircraft, passengers, and crew on September 11, 2001. Since its inception, the Airport and the citizens of the subsequently developed Town of Gander have played an essential role in coordinating and delivering Disaster and Emergency Management (DEM) program services (preparedness, response, mitigation, and recovery) pertaining to aviation disaster and emergency events. Over the past century, the Town of Gander and the Gander International Airport have also been the site of accumulated experiences, learnings, and developed skills from these efforts, all of which have become part of Gander’s unique history and have resulted in the establishment of comprehensive and integrated municipal and airport DEM plans critical to future responses.